Ageism, Personal and Others' Perceptions of Age Awareness, and Their Interactive Effect on Subjective Accelerated Aging. (December 2021) - Bergman, Yoav S.; Palgi, Yuval
Ageism has been associated with negative perceptions of the future and the aging process. The current study argues that this connection is affected by the relevance older adults attribute to the cognitive category of age in their own self-appraisal, as well as by how they perceive this awareness in others. Accordingly, we examined the association between ageism and subjective accelerated aging (i.e., the rate the individual feels he or she is aging) and the moderating role of self-age awareness and other-age awareness on this connection. Data were collected from 267 participants (age range = 40–95; M = 64.32, SD = 14.09), using scales assessing ageism, self/other age awareness, and subjective accelerated aging. High ageism levels were associated with increased subjective accelerated aging. Moreover, this connection was moderated by both self- and other-age awareness. The study enhances the importance of personal appraisals of one's own and others' behaviors as age-related in this context.